Neurorestorative Effect of Urinary Bladder Matrix-mediated Neural Stem Cell Transplantation Following Traumatic Brain Injury in Rats - Wang, JY (2013)
Traumatic brain injury (TBI) is a leading cause of cell death and disability among young adults and lacks a successful therapeutic strategy. The multiphasic injuries of TBI severely limit the success of conventional pharmacological approaches. Recent successes with transplantation of stem cells in bioactive scaffolds in other injury paradigms provide new hope for the treatment of TBI. In this study, we transplanted neural stem cells (0.5×10(5) cells/μl) cultured in a bioactive scaffold derived from porcine urinary bladder matrix (UBM; 4 injection sites, 2.5μl each) into the rat brain following controlled cortical impact (CCI, velocity, 4.0 m/sec; duration, 0.5 sec; depth, 3.2mm). We evaluated the effectiveness of this strategy to combat the loss of motor, memory and cognitive faculties. Before transplantation, compatibility experiments showed that UBM was able to support extended proliferation and differentiation of neural stem cells. Together with its reported anti-inflammatory properties and rapid degradation characteristics in vivo, UBM emerged to be an ideal scaffold. The transplants reduced neuron/tissue loss and white matter injury, and also significantly ameliorated motor, memory, and cognitive impairments. Furthermore, exposure to UBM alone was sufficient to decrease the loss of sensorimotor skills from TBI (examined 3–28 days post-CCI). However, only UBMs that contained proliferating neural stem cells helped attenuate memory and cognitive impairments (examined 26–28 days post-CCI). In summary, these results demonstrate the therapeutic efficacy of stem cells in bioactive scaffolds against TBI and show promise for translation into future clinical use.